2020
DOI: 10.1055/a-1233-1934
|View full text |Cite
|
Sign up to set email alerts
|

Results of liver and spleen endoscopic ultrasonographic elastography predict portal hypertension secondary to chronic liver disease

Abstract: Background and study aims Assessment of endoscopic ultrasonography (EUS)-elastography of the liver and spleen may identify patients with portal hypertension secondary to chronic liver disease. We aimed to evaluate use of EUS-elastography of the liver and spleen in identification of portal hypertension in patients with chronic liver disease. Patients and methods This was a single-center, diagnostic cohort study. Consecutive patients with liver cirrhosis and portal hypertension underwent EUS-elastograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Similar findings were also shown with EUS-elastography of the spleen through strain ratio, which demonstrated slightly higher accuracy (sensitivity 87.5%, specificity 69%, PPV 75.7%, NPV 83.3%) compared to spleen strain histogram (sensitivity 56.3%, specificity 89.7%, PPV 85.7%, NPV 65%). In addition, this study showed that in alcohol-related cirrhotic patients, the combination of an azygos vein diameter higher than 7.6 mm, mean velocity higher than 5.8 cm/s, or blood-flow volume index (BFVI) higher than 2.75 mm 3 /s yielded 100% sensitivity and 100% NPV in predicting PHT, suggesting that a combination of EUS-elastography and azygos vein evaluation can enhance the diagnostic accuracy of each modality [41]. Overall, EUS has been demonstrated to improve diagnostic accuracy in elastography examinations of liver tissues, especially in differentiating between benign and malignant tissues [42].…”
Section: Eus-guided Elastographymentioning
confidence: 84%
“…Similar findings were also shown with EUS-elastography of the spleen through strain ratio, which demonstrated slightly higher accuracy (sensitivity 87.5%, specificity 69%, PPV 75.7%, NPV 83.3%) compared to spleen strain histogram (sensitivity 56.3%, specificity 89.7%, PPV 85.7%, NPV 65%). In addition, this study showed that in alcohol-related cirrhotic patients, the combination of an azygos vein diameter higher than 7.6 mm, mean velocity higher than 5.8 cm/s, or blood-flow volume index (BFVI) higher than 2.75 mm 3 /s yielded 100% sensitivity and 100% NPV in predicting PHT, suggesting that a combination of EUS-elastography and azygos vein evaluation can enhance the diagnostic accuracy of each modality [41]. Overall, EUS has been demonstrated to improve diagnostic accuracy in elastography examinations of liver tissues, especially in differentiating between benign and malignant tissues [42].…”
Section: Eus-guided Elastographymentioning
confidence: 84%
“…Currently, the usefulness of not only semiquantitative EUS–strain elastography but also quantitative EUS–shear wave elastography (EUS-SWE) is being explored. Robles-Medranda (23) measured liver and spleen stiffness by the strain ratio and strain histogram. For identification of patients with cirrhosis and PHT, the liver strain ratio had a sensitivity, specificity, positive predictive value, and NPV of 84.3%, 82.8%, 84.4%, and 82.8%, respectively.…”
Section: Endoscopic Applications In Hepatology Beyond Conventional Sc...mentioning
confidence: 99%